1990
DOI: 10.1007/bf02692149
|View full text |Cite
|
Sign up to set email alerts
|

Teenage childbearing as an alternative life-course strategy in multigeneration black families

Abstract: This paper summarizes the findings of a three-year exploratory qualitative study of teenage childbearing in 20 low-income multigeneration black families. Teenage childbearing in these families is part of an alternative life-course strategy created in response to socioenvironmental constraints. This alternative life-course strategy is characterized by an accelerated family timetable; the separation of reproduction and marriage; an age-condensed generational family structure; and a grandparental child-rearing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
201
2
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(216 citation statements)
references
References 35 publications
11
201
2
2
Order By: Relevance
“…This suggests that a construct such as the unpredictability schema suggested by Ross and Hill (2002) may be a psychological mechanism that catalogues such information from the environment. Perceptual mechanisms aside however, cues to mortality are clearly one of the most important determinants in shaping life history trajectories: studies which have asked respondents to estimate their likely age of death have found significant associations with life history variables (Burton, 1990;DuRant et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that a construct such as the unpredictability schema suggested by Ross and Hill (2002) may be a psychological mechanism that catalogues such information from the environment. Perceptual mechanisms aside however, cues to mortality are clearly one of the most important determinants in shaping life history trajectories: studies which have asked respondents to estimate their likely age of death have found significant associations with life history variables (Burton, 1990;DuRant et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Homicide and age of first birth were strongly related to life expectancy in Chicago's urban neighbourhoods (Wilson & Daly, 1997). Interviews of members of a black community in the United States showed that ninety-one percent of women did not expect to live beyond age sixty, and that the transition to early motherhood was part of an accelerated family timetable calibrated to their assessment of life expectancies (Burton, 1990). proposed.…”
mentioning
confidence: 99%
“…In women, this adaptive shift to a dismissing/short-term strategy may be based in part on several factors: on early reproduction that allows their family members to help raise offspring (Burton, 1990;Lancaster, 1989), on mating with multiple men in order to garner resources or protection from more than one putative father (Hrdy, 1981;Smuts, 1985), and on obtaining access via short-term mating to valuable men possessing ''good genes,'' genes that are better able to withstand the pathogens and developmental stressors of harsh environments (Gangestad, 2001;Gangestad & Simpson, 2000). Thus, women's dismissing romantic attachment levels may be culturally contingent, adaptively shifting in accord with the harsh physical environments (Belsky et al, 1991) and high fertility trends (Chisholm, 1996) of their local ecologies (see also Greiling & Buss, 2000).…”
Section: Evolutionary Psychology and Gender Differences Across Culturesmentioning
confidence: 99%
“…Estudios muestran que las hijas de madres adolescentes tienen entre un 66% y dos veces más el riesgo de llegar a ser madres adolescentes y que se embarazan incluso a edades más tempranas que sus propias madres (28,(30)(31)(32)(33)(34). Las hijas al repetir el patrón reproductivo suman más obstáculos a sus ya escasas posibilidades de movilidad social cerrando de esta manera el círculo de reproducción de la pobreza (35)(36)(37).…”
Section: Introductionunclassified